PhD Review: Dr. Joy Mounter’s PhD Thesis, ‘A Living Educational Theory Research Approach to Continuing Professional Development in Education’. - Jack Whitehead (Educational Journal of Living Theories)
I begin my review by asking you to read Joy Mounter’s abstract to her thesis, in which Joy outlines her original contribution to Living Educational Theory Research with her idea of Living Professionalism. Joy’s Living Educational Theory Research is amongst the most sustained inquiries on an individual’s professional development using a Living Educational Theory approach and also making an original contribution to knowledge of Living Educational Theory Research. The originality will be of use to all practitionerresearchers who are engaged with enhancing their educational influences in the learning of social formations: My research and thesis contribute to the field of the continuing professional development of educational practitioners. The originality of my thesis proposes Living Professionalism as a new professional, values-led Teacher Standard of professionalism, where educational practitioners accept educational responsibility for their own continuing, values-led, professional development. This includes teachers continually researching their practice to improve it, generating values-laden explanations of their educational influence in learning, contributing to the growth of a global educational knowledgebase. I draw on a Living Educational Theory Research methodological approach to continuing professional development in education. My thesis includes evidence of my reflections on the educational influences I have in my own learning, the learning of others and cross social formations, as I accept educational responsibility for my Living Professionalism. I have critically engaged and analysed literature on Living Educational Theory Research,